Demographic variables of Vestibular schwannoma’s patients presented in Radio Surgical out- patient department of Cyberknife Robotic Radiosurgery, JPMC Karachi - Kadri, Shazia; Ahmed, Naveed; Ghulam Muhammad , Aneeta; Saeed, Kamran; Ahmad Hashmi, Syed Furqan; Mahmood , Tariq (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the age, gender and sites of vestibular schwannoma cases using contrast-enhanced magnetic resonance imaging. Method: The retrospective descriptive study was conducted at the Department of Cyberknife Robotic Radiosurgery, Jinnah Postgraduate Medical Centre, Karachi, and comprised data of patients with vestibular schwannomas from January 2016 to September 2018. Some of them were histologically proven and rest were radiologically proven. Cases were reviewed on contrast-enhanced magnetic resonance imaging of the brain. Statistical Package for the Social Sciences version 20 (SPSS) was applied. Results: Of the 500 cases of vestibular schwannomas identified with 515 tumours, 300(60%) were males and 200(40%) were female. The overall mean age was 42.7+/-14.4 years (range: 17-85 years). Out of 515 tumours, the commonest site was the right cerebellopontine angle in 340(66%) cases. There were 15(3%) cases of radiologically-proven neurofibromatosis type 2. Overall, 490(98%) patients had main clinical complaint of progressive unilateral hearing loss, 5(1%) had vertigo and 5(1%) had facial palsy. Conclusion: Vestibular schwannomas were found to be more common among adults, with male preponderance and right cerebellopontine angle being the common site. Key Words: Vestibular schwannoma, VS=, Cerebellopontine angle, P angle, MRI, Magnetic resonance imaging, Neurofibromatosis type II, NF II. Continuous...